"Evaluación de la estabilidad genética en plantas micropropagadas de Vaccinium corymbosum L. var. Biloxi “Arándano” mediante marcadores moleculares RAPDs" - Peña Novoa, Juana Blanca (2017)
The production of blueberries in Perú, has demonstrated a high growth in the last years, therefore new technologies have been adopted for obtaining of profitable and competitive crops. Among them, the in vitro micropropagated, this has developed with great success, getting a great quantity of plants in less time and free of pathogenic agents as virus, fungi and others. However, some of the cultivation in vitro techniques can provoke alterations in the hereditary material, so it's important to determine if they are stable genetically. The aim of this study it is to use molecular markers RAPDs to analyze the stability genetic in micropropagated plants of blueberries "Biloxi" variety. The micropropagated plants were obtained from axillary buds of mother plants in field. It took 0.1 g of leaf tissue of each blueberry plant, for its extraction of DNA, according to the CTAB method. 5 primers were used for the molecular analysis, remaining as the most informative the AB-03 and AB-04. Using electrophoresis on a 4 %, polyacrylamide gel, stained with silver nitrate and it was interpreted the electrophoretic profiles, which generated monomorphic bands, indicating a high degree of monomorphism. In the other hand, based on Jaccard and Nei's similarity coefficients, where similarity matrix showed 1 pair-wise value between mother plant and micropropagated plant.